1988
DOI: 10.1038/sc.1988.28
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation outcomes in C6 tetraplegia

Abstract: SUlll lll aryThis study reports on the rehabilitation outcome of 69 C6 tetraplegic patients admitted to the Rehabilitation Institute of Chicago during an 8 year period. All patients' last normal level was C6 bilaterally. A 100�point modified Barthel Index was used to obtain measures of functional independence in 15 self�care and mobility tasks. The population consisted of 54 males and 15 females with an average age of 29· 2 years. The average number of days from injury to admission to the rehabilita tion unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Several investigators [28][29][30][31][32][33] have explored the relationship between the level of injury and predicted motor recovery finding that lower functioning neurological levels are associated with greater motor recovery. Others 1,[34][35][36] have established expected functional outcomes associated with neurological levels. The paralyzed veterans of America (PVA) related injury level to functional limitation as reflected in performance of motor FIM tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators [28][29][30][31][32][33] have explored the relationship between the level of injury and predicted motor recovery finding that lower functioning neurological levels are associated with greater motor recovery. Others 1,[34][35][36] have established expected functional outcomes associated with neurological levels. The paralyzed veterans of America (PVA) related injury level to functional limitation as reflected in performance of motor FIM tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study was not large enough to investigate how sensory function adds to the variance of ADL performance explained by UEMS. Other factors such as gender, age, body mass and time since injury, 7,8 together with factors in the environment, 52 also influence the variance in the performance of ADL. These factors must be taken into consideration in the assessment of the cervical SCI patient's level of independence in ADL.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Important prerequisites for ADL are upper extremity function 4,5 and physical capacity. 6 Other important factors are age, gender, body mass, 7 physical fitness, 7,8 motivation, psychosocial status, medical complications 8 and sociocultural background. 9 Earlier studies 5,10 have shown that preserved motor level can predict the ability of patients with cervical SCI to become independent in ADL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, motion becomes more di cult. 9 Tetraplegics whose level is C6 or higher cannot swing their upper limbs su ciently to roll. Paraplegic patients with thoracic or lumbar cord injury cannot push against the¯oor, either, to assist them in rotating, and therefore require more rotatomomentum in the upper part of the body in order to roll.…”
Section: Range Of Motion (Rom) In Trunk (In Passive)mentioning
confidence: 99%